2019
DOI: 10.36685/phi.v5i3.287
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Among Adolescent Males at Pulau Weh, Indonesia

Abstract: Background: Use of tobacco may cause severe diseases like cardiovascular diseases and lung cancer. Smoking is a major threat to public health in many low- and middle-income countries.Objective: The aim of this study is to assess the prevalence of smoking among boys in the age group 13-15 years at Pulau Weh in Indonesia, and identify factors associated with smoking.Methods: A cross-sectional study was conducted of 291 male students, aged 13-15 years, in three participating secondary schools. A modified version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
3
5
0
Order By: Relevance
“…Adolescent age was significantly related to smoking behavior. The results of this study were in line with research conducted by Skulberg et.al which showed that there were differences in the proportion of smoking among adolescents between age groups (Skulberg, Hamid, & Vaktskjold, 2019). The researchers divided adolescents into two age groups, 14 years or less and more than 14 years of age.…”
Section: Variablesupporting
confidence: 90%
See 1 more Smart Citation
“…Adolescent age was significantly related to smoking behavior. The results of this study were in line with research conducted by Skulberg et.al which showed that there were differences in the proportion of smoking among adolescents between age groups (Skulberg, Hamid, & Vaktskjold, 2019). The researchers divided adolescents into two age groups, 14 years or less and more than 14 years of age.…”
Section: Variablesupporting
confidence: 90%
“…The results of this study were also in line with a study in Korea that the classification of residence in rural, urban, and metropolitan cities did not affect adolescent smoking behavior (Kim et al, 2013). However, differences with the study by Skulberg found that the odds of being an active smoker were 7.4 times higher among students at the public rural school, as compared to the public school in town (Skulberg et al, 2019).…”
Section: Variablesupporting
confidence: 88%
“…According to a study conducted by Skullberg et al (2019) in Weh Island, Indonesia, having siblings and parents who smoked increased the risk factors for smoking in adolescents. More than a third of boys in the 13-15 year-age group were found to smoke.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Several factors are associated with tobacco use behavior such as age, sex, educational attainment, economic status, residential geographic condition, and family member influence. [7][8][9] Various studies on factors driving tobacco consumption have been conducted in Indonesia. [7,8,10] The results were mostly in conjunction with other studies conducted around the world.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Various studies on factors driving tobacco consumption have been conducted in Indonesia. [7,8,10] The results were mostly in conjunction with other studies conducted around the world. However, very few (if not none) of them investigated the correlation between cultural and religious factors, such as ethnic identity and religion, with tobacco consumption using nationally representative data.…”
Section: Introductionmentioning
confidence: 99%